Biochemical Properties, Mechanisms of Action, and Applications of Papain in Dengue Treatment: Review Article (Journal of Pharma Insights and Research, 2025)
Carica papaya contains several bioactive compounds, with papain being a crucial cysteine protease enzyme found predominantly in its latex. Recent studies indicate that C. papaya leaf extract demonstrates potential therapeutic effects in dengue treatment, particularly in increasing platelet counts. Clinical trials across Asian countries report significant platelet count improvements in dengue patients treated with C. papaya leaf extract. Papain, a 24.5 kDa protein with three disulfide bridges and an essential sulfhydryl group, exhibits optimal activity at temperatures between 50-59°C and pH 4.5-6.7. The enzyme's mechanism involves the Cys-25 region attacking peptide chain carbonyl carbons, with His-159 and Asn-175 playing crucial supporting roles. Metal ions like Mg²⁺ significantly enhance papain activity, while specific inhibitors can modulate its function. The enzyme maintains stability under various conditions, including exposure to certain denaturing agents. Structural analyses reveal two distinct domains with an active site located in the interfacial cleft. The enzyme's hydrophobic core, formed by amino acids like alanine, leucine, and isoleucine, contributes to its stability and functionality. While preliminary evidence supports C. papaya's role in dengue treatment, additional large-scale clinical trials are essential to establish its therapeutic efficacy and safety profile definitively